THE KINDS OF DISCIPLINE APPLIED PARENTS IN PARENTING IN PERAWANG, TUALANG SUB-DISTRICT,SIAK REGENCY” - Rahmi, Siti Ardianti Rahmi Ardianti; Maemunaty, Titi Maemunaty Titi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The study proposed to find out the kinds of Discipline applied Parents in Parenting in Perawang, Tualang Sub-District,Siak Regency. The study used descriptive research with quantitative approach. This study used a descriptive study with a quantitative approach. This method proposed to give an overview of the state of the ongoing research on the object of the kinds of discipline is applied parents in parenting. The data collection technique of this study was the observation and questionnaires. Data obtained from the questionnaire, all the statements in the questionnaire were presented in the form of a Likert scale adapted to the statement. The place of this research is in Perawang, Tualang Sub-District,Siak Regency. This study conducted in September 2014- January 2015.The population of this study was the parents who have children aged 6-10 years, totaling 100 people, while a sample was 50 parents. Based on the summary table overview of the kind of discipline applied parents in parentingin Perawang, Tualang Sub-District, Siak Regency, the indicator mean value of Ototarian Discipline was 2.2 with sd 0.93, the mean value of Discipline Permissive was1.94 with sd 0.78, mean value of Democratic Discipline was 2.82 with sd. 0.92.Based on the survey results revealed that the kind of discipline that most applied parents in parenting in Perawang, Tualang Sub-District, Siak Regency was DemocraticDiscipline. Keywords: Discipline, Parents, Parenting